Gross Anatomy and Vascularization of the Brain of Pacarana (Dinomys branickii) - Freitas, Letícia Menezes; Pereira, Kleber Fernando; de Melo, Fabiano Rodrigues; Silveira, Leandro; dos Santos, Odeony Paulo; Sabec Pereira, Dayane Kelly; Alves de Melo, Fabiana Cristina Silveira; Jácomo, Anah Tereza de Almeida; Lima, Fabiano Campos (Acta Scientiae Veterinariae, 2018)
Background: The pacarana lives in South America and has herbivorous and nocturnal habits. It is a rare species with scarce data concerning its morphology and adding more data is important in establishing its vulnerability. The aim was to describe its macroscopic brain anatomy, as well as the brain vascularization. Materials, Methods & Results: Two specimens were available for this study, that were donated post-mortem. The animals were injected with latex and fixed with 10% formaldehyde. Upon exposure and removal of the brain its main features were described. The rhinal fissure is single and the lateral sulcus arises from its caudal part. There are two sagittal sulci, an extensive medial sulcus and a short lateral sulcus. The piriform lobe is vermiform and the rostral part is smaller. The caudal colliculus is larger than the rostral colliculus and they are separated by a sulcus. The cerebellum has oval shape and the flocculus lobe is not conspicuous. The cerebral arterial circle was analyzed and described. The brain is supplied by the vertebrobasilar system only. The cerebral arterial circle is formed by the terminal branch of the basilar artery, the caudal communicating artery, the rostral cerebral artery and the rostral communicating artery. The caudal and middle cerebellar arteries are branches of the basilar artery. The terminal branch of the basilar artery originates the rostral cerebellar artery and the caudal cerebral artery. From the end of the caudal communicating artery and the beginning of the rostral cerebral artery arises the middle cerebral artery. Discussion: The cerebral structures related to sensory inputs reflect the species usage of senses, or rather one is intrinsically correlated to the other. The caudal colliculus is larger than the rostral colliculus, as the former is related to hearing and the latter to the vision, this indicates that the visual sense is not so important. Indeed, the animals are nocturnal and have small eyes. The hearing on the other hand is used in social interactions, to indicate combat, threat and defensive situations, for example. The rhinencephalon has the most conspicuous external sensory structures and the animals use olfaction for social behaviors, even producing a gland exudate to mark territory. Most brain features are similar with other species in the infraorder Caviomorpha. The brain of the pacarana resembles the brains of the Patagonian mara, capybara and guinea pig. The common porcupine presents a different shape to the brain. The guinea pig and the common porcupine are lissencephalic. The animals that present sulci in the brain, follow this order from more to less girencephalic: capybara, mara and pacarana. The rhinal fissure is important because it delimits the rhinencephalon and it is present in all the animals mentioned above. In the mara, the colliculi are exposed in dorsal and lateral views, however, this does not happen for the pacarana. The cerebellum is similar in these species, but the flocculus is more pronounced in the guinea pig. The brain of Caviomorpha species is supplied only by the vertebrobasilar system in most species analyzed, as in the capybara, guinea pig, coypus, mara, chinchilla, degu and in pacarana, where the absence of the carotid artery was observed. In some species the rostral cerebral artery anastomosis in a single branch that runs towards the corpus callosum (degu, capybara, chinchilla and coypus), but in the pacarana the rostral cerebral artery is present in both left and right sides, then branching towards the corpus callosum and the splenial sulcus. In summary, the pacarana presents brain features similar to other Caviomorpha, with some specific species variation.